2019
DOI: 10.1055/s-0039-1692198
|View full text |Cite
|
Sign up to set email alerts
|

Effect and Complications of Everolimus Use for Giant Cardiac Rhabdomyomas with Neonatal Tuberous Sclerosis

Abstract: Most cardiac rhabdomyomas with tuberous sclerosis (TS) are asymptomatic and spontaneously regress. However, some cases require surgical intervention due to arrhythmia and severe obstruction of cardiac inflow or outflow. We report herein a neonatal case of giant cardiac rhabdomyomas with TS and insufficient pulmonary blood flow from the right ventricle. Lipoprostaglandin E1 was necessary to maintain patency of the ductus arteriosus. We used everolimus, a mammalian target of rapamycin inhibitor, to diminish the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 25 publications
1
10
0
1
Order By: Relevance
“…One study classified as “other” was excluded as it was a notifying article about the planned randomized study of everolimus in CRs treatment [ 23 ]. Overall, 30 reports were included in the systematic review [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ]. Three of the included articles partially duplicated the case reports [ 24 , 34 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One study classified as “other” was excluded as it was a notifying article about the planned randomized study of everolimus in CRs treatment [ 23 ]. Overall, 30 reports were included in the systematic review [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ]. Three of the included articles partially duplicated the case reports [ 24 , 34 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…In 7 studies, authors reported more or less precise size of CR in more than one time point [ 24 , 26 , 36 , 43 , 46 , 47 , 52 ]. The reliable calculation of the correlation between treatment duration and CR reduction was impossible due to data reporting discrepancy and the risk of bias.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Having examined the series of published cases using mammalian target of rapamycin inhibitors for haemodynamically significant rhabdomyomas, these agents are clearly efficacious with all cases showing reduction in size or full resolution of cardiac rhabdomyoma. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][26][27][28][29][30]32,33 However, these drugs are not without risk, and standardised dosing and treatment duration regimens remain to be defined. From the published case reports to date, there is no general consensus on dose of mammalian target of rapamycin inhibitors (variations from 0.1 mg OD to 0.25 mg BD twice per week to 0.5 mg BD twice per week).…”
Section: Discussionmentioning
confidence: 99%
“…Everolimus has been successfully used off-label in pediatric case reports of symptomatic CRs associated with TSC [ 7 , 8 , 9 ]. The optimal dosage for neonates is still unknown and is currently under debate [ 3 , 5 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%